Stigmatising Attitudes among People Offered Home-Based HIV Testing and Counselling in Blantyre, Malawi: Construction and Analysis of a Stigma Scale - MacPherson, Peter (Public Library of Science, 2011)
BACKGROUND: HIV/AIDS related stigma is a major barrier to uptake of HIV testing and counselling (HTC). We assessed the extent of stigmatising attitudes expressed by participants offered community-based HTC, and their anticipated stigma from others to assess relationship with HIV test uptake. From these data, we constructed a brief stigma scale for use around the time of HIV testing. METHODS AND FINDINGS: Adult members of 60 households in urban Blantyre, Malawi, were selected using population-weighted random cluster sampling and offered HTC with the option to self-test before confirmatory HTC. Prior to HTC a 15-item HIV stigma questionnaire was administered. We used association testing and principal components analysis (PCA) to construct a scale measure of stigma. Of 226 adults invited to participate, 216 (95.6%) completed questionnaires and 198/216 (91.7%) opted to undergo HTC (all self-tested). Stigmatising attitudes were uncommon, but anticipated stigma was common, especially fearing verbal abuse (22%) or being abandoned by their partner (11%). Three questions showed little association or consistency with the remaining 12 stigma questions and were not included in the final scale. For the 12-question final scale, Cronbach's alpha was 0.75. Level of stigma was not associated with previously having tested for HIV (p = 0.318) or agreeing to HTC (p = 0.379), but was associated with expressed worry about being or becoming HIV infected (p = 0.003). CONCLUSIONS: Anticipated stigma prior to HTC was common among both men and women. However, the high uptake of HTC suggests that this did not translate into reluctance to accept community-based testing. We constructed a brief scale to measure stigma at the time of HIV testing that could rapidly identify individuals requiring additional support following diagnosis and monitor the impact of increasing availability of community-based HTC on prevalence of stigma.